Dyneins : structure, biology and disease - King, Stephen M. (Academic Press, 2012)
Research on dyneins has a direct impact on human diseases, such as viruses and cancer. With an accompanying website showing over one hundred streaming videos of cell dynamic behavior for best comprehension of material, Dynein: Structure, Biology and Disease is the only reference covering the structure, biology and application of dynein research to human disease. From bench to bedside, Dynein: Structure, Biology and Disease offers research on fundamental cellular processes to researchers and clinicians across developmental biology, cell biology, molecular biology, biophysics, biomedicine, genetics and medicine. . Broad-based up-to-date resource for the dynein class of molecular motors . Chapters written by world experts in their topics . Numerous well-illustrated figures and tables included to complement the text, imparting comprehensive information on dynein composition, interactions, and other fundamental features.